Estruturação genética em populações do tangará-dançarino Chiroxiphia caudata (Aves, Pipridae) no corredor costeiro da Mata Atlântica (SP) e sua importância para a conservação - Francisco, Mercival Roberto (Universidade Federal de São Carlos, 2005)
Neotropical passerine birds that inhabit forests understory are thought to be highly sedentary, which may result in greater genetic differentiation among populations than in temperate species. The species of the genus Chiroxiphia (Pipridae) perform highly specialized courtship displays in which males aggregate at traditional arenas, or ``leks´´, performing a precopulatory dance. Each lek consists of 2-6 males, where a linear dominance hierarchy exists. With rare exceptions, the dominant male perform all of the copulations, resulting in one of the highest variances in male mating success ever demonstrated in vertebrates. Since subordinate males (beta) expend energy dancing, increasing the fitness of the alpha male, without receiving any immediate benefit, it has been hypothesized that kin selection could be involved, providing a genetic payoff to the subordinate individuals. Considering that the leks locations are permanent, if kin selection is involved, male dispersal is expected to be limited at some level, while females, that are free to visit different leks, would be the more dispersive sex. Sedentariness associated with the high variance in male mating success, as well as the possibility of kin selection, make of these birds candidates to present high levels of interpopulation structuring. In this work we investigated the extent of variation within and among blue-manakin, Chiroxiphia caudata, populations using 10 polymorphic microsatellite loci, along a 415 km transect, which covers most of the extension of the largest remaining continuum of one of the most endangered ecosystem in the planet, the Brazilian Atlantic forest. Low but significant levels of differentiation were found across populations (FST = - 0.0002 to 0.023). This structuring must be mostly related to social aspects of the species, and three non exclusive hypothesis can be urged to explain it: (1) genetic drift due to the intra population smaller effective population size caused by the high variance in male mating success; (2) inbreeding if males contribute to more than one generation of females and (3) the existence of kin selection among males from the same lek. Besides, an isolation by distance pattern of differentiation was found, indicating that dispersal is at some level limited, which can also have contributed to the observed structuring. Thus, a significant part of the blue manakin genetic diversity was distributed among populations, even at such a limited geographic scale. When these continuous areas get disconnect reducing gene flow, these animals are probably much more prone to suffer inbreeding depression and loose alleles than species that are not naturally inbred, such as most of the temperate birds. In this scenario, preserving continuous areas must be essential to maintain the genetic diversity, and the continuous corridor here studied can be the last large genetic repository for many Atlantic forest organisms.
Keywords: Aves; Conservação (Biologia); Mata Atlântica; Microssatélites; Genética - conservação; CIENCIAS BIOLOGICAS::ECOLOGIA